Job insecurity, subjective well-being and job performance: the moderating role of growth mindset - Epic Anung Anindita Setjo; Rosaly Franksiska (Diponegoro International Journal of Business, 2021)
This study aims to analyze the impact of job insecurity on subjective well-being and the impact on job performance, with a growth mindset as the moderating variable.  The COVID-19 pandemic has been running for more than 1 year and this research was conducted during the pandemic period. Due to the COVID-19 pandemic, many companies and other units were adversely affected so that the companies’ performance declined, PT Armada Finance is one of those. Therefore, this study expected that job insecurity influences subjective well-being, and subjective well-being influences job performance. Furthermore, a growth mindset is also expected to have a moderating influence on the subjective well-being of the employees to increase job performance. The results of regression and moderated regression analysis (MRA) on 75 samples collected from employees of PT Armada Finance company in Magelang, Central Java, Indonesia, show that job insecurity does not influence subjective well-being. The result also shows that subjective well-being has a positive influence on job performance. In addition, this study also suggests that having a growth mindset could be moderating subjective well-being to increase job performance.